Green, Green Grass of Home - Boynton, Te Atamea (Te Kaharoa, 2021)
Our old grey Subaru crept slowly up the dusty gravel road. It was a muggy evening, but you couldn’t turn the air con on or open any windows unless you wanted a car full of dust. I got to sit in the front for this last stretch to Nanny’s, so I oversaw switching out Dad's Prince Tui Teka CDs. Dad went extra slow so as not to scratch the discs, but that was hard on a gravelly road full of potholes.